Individualizing Prevention for Older Adults - Lee, Sei J. (J Am Geriatr Soc, 2017)
Prevention can help older patients avoid illness by identifying and addressing conditions before they cause symptoms. However, prevention can also harm older patients if conditions that are unlikely to cause symptoms in the patient’s lifetime are identified and treated. To identify older patients who are most likely to benefit (and most likely to be harmed) by preventive interventions, we propose a framework that compares a patient’s life expectancy (LE) with the time to benefit (TTB) for an intervention. If the LE << TTB, the patient in unlikely to benefit but is exposed to the risks of the intervention. Thus, the intervention should generally NOT be recommended. If the LE >> TTB, the patient could benefit and the intervention should generally be recommended. If the LE ~ TTB, the decision is a “close call” and the patient’s values and preferences should be the major driver of the decision. To facilitate the use of this framework in routine clinical care, we 1) explore ways to estimate LE, 2) identify the TTB for common preventive interventions and 3) recommend strategies for communicating with patients. We synthesize these strategies and demonstrate how they can be used to individualize prevention for a hypothetical patient in the setting of a Medicare Annual Wellness Visit. Finally, we place prevention in the context of curative and symptom-oriented care and outline how prevention should be focused on healthier older adults, while symptom-oriented care should predominate in sicker older adults.